What Reduces Switching Behavior in Indonesian Islamic Banking? The Mediating Role of Customer Satisfaction - Hildah Meliyana; Elfira Maya Adiba; Dahruji (Universitas Muhammadiyah Surakarta, 2026)
Switching behavior is a marker of customer loyalty, particularly among Islamic bank customers. Therefore, a strategy is needed to reduce the rate of customer switching from an Islamic bank to other banks. This study aims to analyze the determinants of switching behavior in Indonesian Islamic banks, using customer satisfaction as a mediating variable. This study employed a quantitative approach using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). This study successfully collected primary data from 265 customers of an Indonesian Islamic bank. The results of this study indicate that none of the antecedent variables directly influence switching behavior, but they do significantly influence customer satisfaction. Customer satisfaction effectively mediates switching behavior, indicating that more satisfied customers are less likely to switch banks. The findings of this study indicate that Islamic bank customers act rationally by evaluating all antecedent variables before switching to another bank. This research theoretically contributes to the literature regarding the importance of customer satisfaction in explaining customer behavior. In practice, this research emphasizes the need for appropriate strategies to provide a positive experience of transacting with Islamic banks, thereby satisfying customers and minimizing switching behavior. Therefore, banks must maintain and improve customer satisfaction through optimizing competitive profit-sharing schemes, service strategies, sharia compliance, and technological innovation to increase customer loyalty and reduce switching behavior. This strategy is expected to strengthen Islamic banks’ long-term competitiveness.